Para além do parto : a manutenção-mudança das práticas obstétricas - Júlio, Ana Carolina (2019)
This PhD. dissertation aims to analyze how obstetrical practice organization motivates the practitioners (not) to opt for a “humanized” normal birth, contributing to the maintenance and/or the change of giving birth as a social practice. I used the practi